(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
The legal regulation of administrative acts constitutes one of the central elements of public administration, as such acts serve as instruments through which public authorities create, modify, or terminate individual public-law relationships. Despite the fundamental role administrative acts play in ensuring lawful governance, the issue of their legal defects—particularly the distinction between nullity and invalidity—remains insufficiently developed in contemporary administrative law. This doctrinal uncertainty is especially evident in the legislation of the Republic of Uzbekistan, where the legal consequences of defective administrative acts are not clearly differentiated, thereby creating ambiguity in law enforcement practice and weakening legal certainty.